How do beliefs about the gender wage gap affect the demand for public policy? - Sonja Settele (University of Bonn and University of Cologne, Reinhard Selten Institute (RSI), 2022)
I conduct a survey experiment to study the relationship between people's beliefs about the size of the gender wage gap and their demand for policies aimed at mitigating it. Beliefs causally affect support for equal pay legislation and affirmative action programs, but cannot account for the polarization in policy views by partisanship and gender. Changes in policy demand seem to be driven by changes in beliefs about discrimination in labor markets and fairness concerns, while self-interest appears less important. I provide evidence that pessimism about the effectiveness of government intervention limits the elasticity of policy demand to perceived wage differentials.
Keywords: 330